Comparative Outcomes of Ginger Decoction and Lavender Aromatherapy on Emesis Gravidarum Among First-Trimester Pregnant Women: A Quasi-Experimental Study - Tahun, Omega DR; Rahman, Eka Yuniarti; Putri, Ayu Tiara (Chakra Brahmanda Lentera Institute, 2026)
Background: Emesis gravidarum affects 60–80% of first-trimester pregnancies and can reduce maternal quality of life. Evidence comparing ginger decoction and lavender aromatherapy remains limited, particularly in Indonesian primary maternal healthcare settings. This study compared their effectiveness in reducing the severity of emesis gravidarum among first-trimester pregnant women. Methods: A quasi-experimental design with two separate intervention groups was employed, adhering to Transparent Reporting of Evaluations with Nonrandomized Designs (TREND) guidelines. Forty-four first-trimester pregnant women (≤12 weeks' gestation) experiencing emesis gravidarum were recruited via purposive sampling from Independent Midwifery Clinics in East Jakarta and Bekasi, Indonesia (November–December 2025). Group 1 (n=22) received ginger decoction; Group 2 (n=22) received lavender aromatherapy. The independent variable was intervention type; the dependent variable was emesis gravidarum severity, measured by the Pregnancy Unique Quantification of Emesis/Nausea (PUQE) instrument. Data were analysed using the Independent T-test, the Wilcoxon signed-rank test, and Cohen's d for effect size. Results: Post-intervention mean PUQE score was significantly lower in the ginger decoction group (Mean=5.50, SD=1.50) versus lavender aromatherapy (Mean=7.18, SD=1.62; p=0.001; Mean difference=1.68; 95% CI: 0.73–2.63; Cohen's d=0.76). Both interventions significantly reduced emesis severity from pre- (Mean=9.34, SD=1.72) to post-intervention (Mean=6.34, SD=1.75; p<0.001, Wilcoxon test). Conclusion: In this quasi-experimental study, ginger decoction demonstrated superior outcomes, serving as a low-cost, culturally adaptable non-pharmacological option for emesis gravidarum in Indonesian primary maternal healthcare. Lavender aromatherapy provided meaningful complementary benefit, particularly for women with psychosocial contributors to nausea or those intolerant of ginger. Findings should be interpreted within the limitations of the quasi-experimental design and the limited geographic scope.